Double-sided balanced conditional Sharpe ratio - Saeid Tajdini; Mohsen Mehrara; Reza Tehrani (Cogent Economics & Finance, 2019)
The purpose of this study was to investigate the behavior of various indices of Tehran Stock Exchange firstly in the boom period from 2018-03-21 to 2018-11-02 and secondly in the recession period from 2016-03-20 to 2016-12-20 using double-sided balanced conditional Sharpe ratio. The results of this study showed the best performance for the insurance index with a double-sided balanced conditional Sharpe ratio of 0.123 and later for the metallic minerals index with a measure of 0.1215. Moreover, on the basis of the double-sided balanced conditional Sharpe ratio, the food except for sugar index with a measure of 0.035 showed the worst performance.